2015
DOI: 10.1016/j.jalz.2015.07.492
|View full text |Cite
|
Sign up to set email alerts
|

Multisite assessment of NIA‐AA guidelines for the neuropathologic evaluation of Alzheimer's disease

Abstract: INTRODUCTION Neuropathologic assessment is the current “gold standard” for evaluating the Alzheimer’s disease (AD), but there is no consensus on methods used. METHODS Fifteen unstained slides (eight brain regions) from each of the fourteen cases were prepared and distributed to ten different National Institute on Aging AD Centers for application of usual staining and evaluation following recently revised guidelines for AD neuropathologic change. RESULTS Current practice used in the AD Centers program achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 14 publications
7
99
1
Order By: Relevance
“…2a–b). Semi-quantitative analyses of LBs and GCIs 15,16 stained by Syn7015 or Syn303 on adjacent sections showed that Syn7015 preferentially recognized GCIs over LBs (Fig. 1e), which was also supported by the ratio of total area occupied by Syn7015+ over Syn303+ pathology (Fig.…”
Section: Main Textmentioning
confidence: 57%
“…2a–b). Semi-quantitative analyses of LBs and GCIs 15,16 stained by Syn7015 or Syn303 on adjacent sections showed that Syn7015 preferentially recognized GCIs over LBs (Fig. 1e), which was also supported by the ratio of total area occupied by Syn7015+ over Syn303+ pathology (Fig.…”
Section: Main Textmentioning
confidence: 57%
“…Replication of our findings in an independent prospective cohort is needed to further interpret the generalizability of results; however, we used a bootstrapped random patient selection procedure to reduce overfitting of our models. Finally, the neuropathological data were collected at autopsy from multiple centers using different staining procedures; however, we used standardized methods—used across >30 NIH/NIA-funded Alzheimer’s centers in the National Alzheimer’s disease Coordinating Center https://www.alz.washington.edu/ —for merging multi-center data which provide reliability across participating institutions to reduce inter-lab variability, 4,13 and the neuropathological methods and criteria used here were recently validated in a large multi-center study 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also aim to re-evaluate these observations to validate this approach and to develop a concise classification of ARTAG for diagnostic neuropathology. To reach this goal, paradigms will need to be designed for ARTAG along the lines used to standardize evaluation and diagnostic criteria for tau, amyloid and α-synuclein and other major pathologies [24, 10, 45]. Subsequently, it will be possible to evaluate inter-rater reliability of the proposed evaluation and eventually to merge clinical and pathologic data from multiple centers to determine practical significance of ARTAG.…”
Section: Discussionmentioning
confidence: 99%